PENGARUH PROFITABILITAS, TINGKAT HUTANG, DAN UKURAN PERUSAHAAN TERHADAP BOOK TAX GAP PADA PERUSAHAAN SUB-SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2012-2015 - Riansa, Ikhsan; Rahmawaty, Rahmawaty (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
This study aims to examine the influence of probitability, leverage, and firm size to book tax gap. The samples of this research are the Sub-Sektor Property and Real Estate firms listed in BEI (Bursa Efek Indoensia) in 2012-2015. The Samplesare collected using purposive sampling method and resulted 32 companies become the finalsamples. Data was analised by using the multiple regression analysis. The results of this research show that (1) profitability, leverage, and firm size simultaneously influence for book tax gap, (2) profitability has positive influence and significantonbook tax gap, (3) leveragenegatively influence and significantonbook tax gap, and (4) firm size positively influence and significant on book tax gap.